Analisis SWOT dalam Pengembangan Bisnis Berbasis Sustainability Melalui Strategi Word of Mouth (WOM) pada Peternak Ayam Petelur Makmur Farm di Kabupaten Tulungagung - Sega Rohma Nur Ulaika; Anas Firman Adi; Priska Wulan Ndari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of Makmur Farm's poultry egg farming business in Tulungagung requires effective strategies to ensure sustainability. This study aims to analyze the role of SWOT analysis and Word of Mouth (WOM) strategy in sustainable business development. A qualitative approach was used, involving data collection through direct observation, in-depth interviews with owners and staff, and documentation at the farm site. Data were analyzed using SWOT to identify strengths, weaknesses, opportunities, and threats faced by the business. Results indicate that Makmur Farm has strengths in product quality and innovation, but faces weaknesses in digital marketing. Significant opportunities arise from increasing public awareness of sustainability and market trends, while threats include competition and feed price fluctuations. The WOM strategy proved effective in building customer confidence and organically expanding market reach. The discussion emphasizes the importance of integrating SWOT analysis with a digital-based WOM strategy and highlights the role of personal communication and trust-building in creating long-term sustainability for the farm. This comprehensive approach supports strategic decision-making and sustainable growth.